2015
DOI: 10.1080/19401493.2015.1004109
|View full text |Cite
|
Sign up to set email alerts
|

On the turbulence models and turbulent Schmidt number in simulating stratified flows

Abstract: Stratified flows are prevalent in indoor and outdoor environments. To predict these flows, this investigation evaluated the performance of seven turbulence models by comparing the simulation results with the experimental data of both weakly and strongly stratified jets. The models tested included six Reynolds-averaged Navier-Stokes models and one large eddy simulation (LES) model. The velocity, turbulent kinetic energy (TKE), and Reynolds stress distributions were examined. For the weakly stratified jet, all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…A linear relationship between Sc t and Ri was proposed, in which Sc t increased with the increasing level of stratification, i.e., with Ri [50,54]. Even, Shi et al [72] noted that the larger the value of Sc t was, the higher the predicted peak density was. This is because the mixing of the two species in the stratified flows was inversely dependent on Sc t .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A linear relationship between Sc t and Ri was proposed, in which Sc t increased with the increasing level of stratification, i.e., with Ri [50,54]. Even, Shi et al [72] noted that the larger the value of Sc t was, the higher the predicted peak density was. This is because the mixing of the two species in the stratified flows was inversely dependent on Sc t .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some of the presented studies suggested that Sc t should be considered as a parameter, which has different values in the same flow domain, but there was no agreement about the parameters controlling this variability in the flow domain. In sediment transport, some studies suggested even an influence of the presence or not of bedforms [41] and of the type of transported particles [43,48], whereas in stratified flow, even the effect of density gradients was observed [50,54,72].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations